Ocorrência sazonal e reprodução de Himantopus mexicanus (Aves: Charadriiformes) em salinas do Estuário do Rio Apodi-Mossoró, nordeste brasileiro - Mendonça, Maria Luiza Andrade (Universidade Federal Rural do Semi-Árido, 2016)
The disorderly coastal occupation has caused the destruction of natural wetlands and induced many populations of shorebirds to use alternative habitats for feeding, resting and breeding. The objectives of this study were to describe and monitor the seasonal occurrence and the breeding of black-necked stilts (Himantopus mexicanus) in artificial saline at Estuary Apodi-Mossoró, RN, Brazil – an alternative habitat used by Nearctic and Neotropical shorebirds. Censuses of individuals, nests and eggs of the black-necked stilt were conducted between August 2012 and December 2015, in an area of ~145ha, at the municipality of Areia Branca (04°57'S; 37°08'W). In addition, an experiment was conducted using artificial nests to identify potential terrestrial nest predators in the study area, and to analyze if the predation rates vary between microhabitats and among the most widely used materials for nest building. The studied population of black-necked stilt presented a defined seasonal occurrence, with individuals coming in study area in March and remained until October of the years 2012, 2013, 2014 and 2015. During three breeding seasons monitored (2013, 2014 and 2015), a total of 47 active nests was recorded, exclusively located in dikes of evaporators ponds of the saline. Coating materials used for natural nests building were shells, salt crystals and vegetation fragments, found in soil near nesting sites. The majority of natural monitored nests was depredated (93.6%). From the experiment with artificial nests was also verified high predation rates in the study area, regardless of microhabitat within the saline or the material used for nest confection. Mammals and birds, including domestics, were the potential predators of artificial nests in saline. The exclusion of domestic animals in saline and surroundings evaporation ponds could be an initial strategy to reduce the high predation rates of shorebirds nests in salines at northeastern Brazil
Keywords: Habitats alternativos; Reprodução; Pernilongo-de-costas-negras; Rio Grande do Norte; Conservação; Alternative habitats; Breeding; Black-necked stilt; Rio Grande do Norte; Conservation; CIENCIAS BIOLOGICAS::ECOLOGIA